Lattice Boltzmann Simulation of Fluid Flow and Heat Transfer in Random Porous Media - Fan Shengqi (E3S Web of Conferences)
In this paper, the lattice Boltzmann method was adopted to numerically simulate the fluid flow and heat transfer characteristics in random porous media. By varying the pressure, Reynolds number and particle surface temperature, the changes in the flow field cloud map, average resistance coefficient, temperature field cloud map and average Nusselt number under different parameters were obtained. Through the construction of a fluid flow and heat transfer model that couples the pressure field and temperature field, the influence of fluid flow and heat transfer in randomly distributed porous media under different conditions was analyzed.